Our experience with topical 5 fluoro uracil in sinonasal neoplasia - Sanyal, Shaoni Dhole; Biswas, Debashis; Raychowdhury, Ranjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Sino-nasal neoplasms account for 3% of all head and neck cancers. Adenocarcinoma of the paranasal sinuses accounts for 9% of all sino-nasal malignancies and is the most common malignancy of the ethmoid sinus. Other neoplasms which involve the ethmoidal sinuses include inverted papilloma and squamous cell carcinoma. Traditionally, the treatment of choice for an adenocarcinoma of the ethmoidal sinuses involved craniofacial resection. This procedure is related with high rates of mortality and morbidity. Knegt et al reported greater success, both in terms of clinical outcome and survival data, with a less aggressive surgical approach coupled with repeated topical 5 fluorouracil (5FU) applications as a chemotherapeutic agent. Over the last 10 years we have treated selected cases of sinonasal neoplasia with a protocol similar to Knegt. Two (adenocarcinoma and inverted papilloma) of our four cases remain well and are on follow-up. The other two (undifferentiated carcinoma) were lost to follow-up. The rarity of sino-nasal neoplasms make them an unlikely subject for a randomised control trial. With that in mind surgical debridement and topical 5 fluorouracil seems to offer an acceptable treatment for adenocarcinoma of the sinonasal tract in properly selected cases. It may also have a role in Squamous cell carcinoma of ethmoidal or maxillary sinus and in preventing recurrence of inverted papilloma.